A composite hydrogel material for blocking co-migration of pollutants carried by biocolloids, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611417746.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明的目的在于提供一种阻断生物胶体携带污染物共迁移的复合水凝胶材料及其制备方法和应用,本发明提供的复合水凝胶材料能够对生物胶体携带型复合污染物实现捕获、解耦、固定和失活,可以解决现有水凝胶吸附材料主要针对游离态污染物、难以处理生物胶体携带型复合污染物的问题
1)复合水凝胶材料不仅能够处理单一游离态污染物,还能对细菌、抗性细菌、胞外聚合物、腐殖质、胶体颗粒携带的复合污染物进行处理;
Smart Images

Figure CN122912755A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogel material preparation, and in particular to a composite hydrogel material that blocks the co-migration of pollutants carried by biocolloids, its preparation method, and its application. Background Technology
[0002] With the increasing use of industrial production, urban sewage discharge, and chemicals such as antibiotics and disinfectants, pollutants in actual water bodies no longer exist in a single free state, but are gradually becoming more complex, colloidal, and biologically carrier-based, resulting in more complex pollutant types, diverse pollution forms, and increased biological risks.
[0003] Heavy metal ions, organic pollutants, colloidal particles, pathogenic microorganisms, resistant bacteria, and extracellular polymers can combine through electrostatic interactions, coordination interactions, hydrophobic interactions, hydrogen bonding, or biofilm encapsulation to form biocolloidal-borne complex pollutants with migratory capabilities. In this type of complex pollution system, bacteria, resistant bacteria, extracellular polymers, humic substances, and colloidal particles can act as pollutant carriers, carrying heavy metal ions, organic pollutants, and resistance-related pollutants through water bodies. Compared to free-state pollutants, these pollutants exhibit stronger environmental stability and migration capabilities, and are more prone to secondary release and biodiversity risk. Traditional water treatment materials can only adsorb free-state metal ions or single organic pollutants, often failing to effectively block the co-migration process of these complex pollutants.
[0004] Existing hydrogel adsorbent materials typically utilize their three-dimensional network structure, high water content, and abundant functional groups to adsorb pollutants such as heavy metal ions, dye molecules, antibiotics, ammonia nitrogen, phosphorus, uranium, and lithium in water. These materials offer certain advantages in pollutant removal; however, most technical approaches primarily focus on the material's adsorption capacity, functional group types, matrix composition, or filler composite method, and primarily treat free-state pollutants. For complex pollutants carried by biocolloids and extracellular polymers in real water bodies, existing hydrogel materials generally lack the ability to preferentially capture pollutant carriers, decouple and release associated pollutants, and confine and immobilize decoupled pollutants.
[0005] Furthermore, some existing functional materials can adsorb, transform, or inactivate specific pollutants through metal hydroxides, composite metal hydroxides, carbon materials, or metal-organic frameworks. However, these materials are often used in the form of powders, granules, or single composite fillers, which leads to problems such as aggregation, loss, insufficient utilization of effective sites, and difficulty in recycling in complex water bodies. Simply incorporating them into hydrogels is still insufficient to effectively solve problems such as co-migration of complex pollutants, masking of associated pollutants, and secondary release. Summary of the Invention
[0006] The purpose of this invention is to provide a composite hydrogel material that blocks the co-migration of pollutants carried by biocolloids, its preparation method, and its application. The composite hydrogel material provided by this invention can capture, decouple, fix, and deactivate biocolloid-carried composite pollutants, which can solve the problem that existing hydrogel adsorption materials are mainly for free pollutants and have difficulty in treating biocolloid-carried composite pollutants.
[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a composite hydrogel material that blocks the co-migration of pollutants carried by biocolloids, comprising a hydrogel network, a biocolloid capture functional unit, a contaminated pollutant decoupling functional unit, and a confined fixation or inactivation functional unit. The biocolloid capture functional unit includes one or more of the following: cationic groups, zwitterionic groups, polyphenolic adhesive groups, amino groups, guanidinyl groups, quaternary ammonium groups, imidazolium groups, phosphate groups, carboxyl groups, catechol groups, and polysaccharide segments; The associated pollutant decoupling functional unit is a functional group or functional chain segment fixed on the hydrogel network; The confined fixation or deactivation functional unit includes a layered composite metal hydroxide.
[0008] Preferably, the hydrogel network comprises a hydrophilic polymer material and water.
[0009] Preferably, the biocolloid capture functional unit is disposed on the surface of the hydrogel network or extends through the hydrogel network.
[0010] Preferably, the mass of the biocolloid capture functional unit is 1 to 40% of the dry mass of the hydrogel network, with the dry mass of the hydrogel network being 100%.
[0011] Preferably, the associated pollutant decoupling functional unit is disposed after or adjacent to the biocolloid capture functional unit.
[0012] Preferably, based on the dry basis mass of the hydrogel network as 100%, the mass of the associated pollutant decoupling functional unit is 0.5~35% of the dry basis mass of the hydrogel network.
[0013] Preferably, the confined fixation or deactivation functional units are distributed in the inner layer, pore walls, or network cross-linking nodes of the hydrogel network.
[0014] Preferably, with the dry basis mass of the hydrogel network being 100%, the mass of the confined, fixed, or deactivated functional unit is 2 to 70% of the dry basis mass of the hydrogel network.
[0015] This invention provides a method for preparing the composite hydrogel material described in the above technical solution, comprising the following steps: (1) Mix the hydrophilic polymer material with water to obtain a hydrogel network precursor solution; (2) The hydrogel network precursor solution obtained in step (1), the functional components containing biocolloid capture functional units, the functional components containing associated pollutant decoupling functional units, and the components containing confined fixation or inactivation functional units are mixed to obtain a hydrogel composite system. (3) The hydrogel composite system obtained in step (2) is sequentially molded, crosslinked, washed and activated to obtain a composite hydrogel material.
[0016] This invention provides the application of the composite hydrogel material described in the above technical solution or the composite hydrogel material prepared by the preparation method described in the above technical solution in water purification.
[0017] This invention provides a composite hydrogel material for blocking the co-migration of contaminants carried by biocolloids, comprising a hydrogel network, biocolloid capture functional units, associated contaminant decoupling functional units, and confined fixation or inactivation functional units. The biocolloid capture functional units include one or more of cationic groups, zwitterionic groups, polyphenolic adhesive groups, amino groups, guanidinyl groups, quaternary ammonium groups, imidazolium groups, phosphate groups, carboxyl groups, catechol groups, and polysaccharide segments. The associated contaminant decoupling functional units are functional groups or functional segments fixed on the hydrogel network. The confined fixation or inactivation functional units include layered composite metal hydroxides. The composite hydrogel material provided by this invention uses a hydrogel network as its framework. A biocolloidal capture unit is used to capture pollutant carriers such as bacteria, resistant bacteria, extracellular polymers, humic substances, and colloidal particles in water. A concomitant decoupling unit weakens the electrostatic, coordination, hydrogen bonding, hydrophobic, and biofilm encapsulation interactions between the pollutant carriers and the heavy metals, metalloids, organic pollutants, or resistance-related pollutants they carry, causing the concomitant pollutants to be exposed, transferred, or released from the surface of the pollutant carriers. A confinement and inactivation unit performs complexation, ion exchange, adsorption, precipitation, mineralization, oxidation, reduction, inhibition, and inactivation on the exposed, transferred, or released concomitant pollutants, thereby blocking the co-migration and secondary release of biocolloidal-carried composite pollutants in water. The biocolloidal capture unit, concomitant pollutant decoupling unit, and confinement and inactivation unit form a continuous action pathway in the hydrogel material for pollutant carrier capture, concomitant pollutant decoupling, and confinement and inactivation of concomitant pollutants. The results of the embodiments show that the composite hydrogel material provided by the present invention achieves the blocking of the co-migration process of composite pollutants through the continuous action of pollutant carrier capture, associated pollutant decoupling, and pollutant confinement fixation or inactivation. It has a good purification effect on composite pollutants in water. In the early stage of treatment, the hydrogel material mainly traps biological colloids, bacteria, extracellular polymers and colloidal particles through surface capture. In the middle stage of treatment, the associated pollutant decoupling functional unit weakens the binding between the pollutant carrier and heavy metal ions or organic pollutants, causing the associated pollutants to be exposed or transferred. In the later stage of treatment, the confinement fixation or inactivation functional unit adsorbs, complexes, precipitates, mineralizes, redox, inhibits or inactivates the exposed pollutants, so that the pollutants are confined inside the hydrogel material, reducing their secondary release and co-migration risk. The turbidity, color, COD, heavy metal ion concentration and bacterial count of the water body are all significantly reduced. Attached Figure Description
[0018] Figure 1 A schematic diagram of the structure of the composite hydrogel material provided by the present invention; Figure 2 This is a schematic diagram of the preparation process of the composite hydrogel material provided by the present invention; Figure 3 A schematic diagram illustrating the mechanism of action of the composite hydrogel material provided by the present invention in water purification; Figure 4 This is a graph showing the trend of the purification effect of the composite hydrogel material on the water body to be treated as the dosage of the composite hydrogel material increases in Example 1. Figure 5 This is a graph showing the trend of the purification effect of the composite hydrogel material on the water body to be treated as the treatment time increases in Example 1. Figure 6 Comparison diagrams showing the treatment effects of the composite hydrogel materials provided in Application Examples 1-7 and Comparative Application Examples 1-3. Detailed Implementation
[0019] This invention provides a composite hydrogel material that blocks the co-migration of pollutants carried by biocolloids, comprising a hydrogel network, a biocolloid capture functional unit, a contaminated pollutant decoupling functional unit, and a confined fixation or inactivation functional unit. The biocolloid capture functional unit includes one or more of the following: cationic groups, zwitterionic groups, polyphenolic adhesive groups, amino groups, guanidinyl groups, quaternary ammonium groups, imidazolium groups, phosphate groups, carboxyl groups, catechol groups, and polysaccharide segments; The associated pollutant decoupling functional unit is a functional group or functional chain segment fixed on the hydrogel network; The confined fixation or deactivation functional unit includes a layered composite metal hydroxide.
[0020] The composite hydrogel material provided by this invention includes a hydrogel network; the hydrogel network preferably comprises a hydrophilic polymer material and water. In this invention, the hydrophilic polymer hydrogel network serves as the main body of the hydrogel material, providing continuous water-containing channels, mechanical support, and space for fixing functional units.
[0021] In this invention, the hydrophilic polymer material is preferably one or more of natural polymers, synthetic polymers, and composite polymer materials; the natural polymers preferably include one or more of bacterial cellulose, nanocellulose, carboxymethyl cellulose, sodium alginate, chitosan, carboxymethyl chitosan, gelatin, starch, lignin derivatives, pectin, carrageenan, xanthan gum, and hyaluronic acid; the synthetic polymers preferably include one or more of polyvinyl alcohol, polyacrylamide, polyacrylic acid, polyacrylate, polyacrylamide-acrylic acid copolymer, polyethyleneimine-modified polymer, and zwitterionic polymers; the composite polymer material preferably includes a combination of natural and synthetic polymers; the water is preferably deionized water. This invention does not impose any particular limitation on the ratio of natural to synthetic polymers in the composite polymer material; any ratio can be used.
[0022] In this invention, the weight-average molecular weight of the natural polymer is preferably 1 × 10⁻⁶. 4 Da~5×10 6 Da, more preferably 5×10 4 Da~2×10 6 Da; the degree of polymerization of the natural polymer is preferably 100~50000, more preferably 500~20000; the weight-average molecular weight of the composite polymer material is preferably 1×10 4 Da~3×10 6 Da, more preferably 5×10 4 Da~2×10 6 Da; the degree of polymerization of the composite polymer material is preferably 100~20000, more preferably 500~10000; the weight-average molecular weight of the synthesized polymer is preferably 1×10 4 Da~5×10 6 Da, more preferably 5×10 4 Da~2×10 6 Da; the degree of polymerization of the synthesized polymer is preferably 100~50000, more preferably 500~20000. In the embodiments of the present invention, the degree of polymerization of the bacterial cellulose, nanocellulose and carboxymethyl cellulose can independently be 100~20000, or even 500~10000; the weight-average molecular weight of the sodium alginate, chitosan, carboxymethyl chitosan, pectin, carrageenan, xanthan gum and hyaluronic acid can independently be 1×10 4 Da~3×10 6 Da can also be 5×10 4 Da~1.5×10 6 Da; the degree of polymerization of the polyvinyl alcohol can be 500~5000, or 1000~3000; the weight-average molecular weight of the polyacrylamide, polyacrylic acid, polyacrylate, and polyacrylamide-acrylic acid copolymer can independently be 5×10 4 Da~5×10 6 Da can also be 1×10 5 Da~2×10 6 Da; The weight-average molecular weight of the polyethyleneimine-modified polymer and the zwitterionic polymer can independently be 1 × 10⁻⁶. 4 Da~2×10 6 Da can also be 5×10 4 Da~1×10 6In this invention, the molecular weight and degree of polymerization of the hydrophilic polymer material should meet the requirements of forming a stable hydrogel network, maintaining continuous water-containing channels, and fixing each functional unit. If the molecular weight or degree of polymerization of the hydrophilic polymer material is too low, the resulting hydrogel network will lack strength and is prone to swelling and breakage, loss of functional units, or unstable fixation of contaminants; if the molecular weight or degree of polymerization is too high, the viscosity of the precursor liquid will be too high, which is not conducive to the uniform dispersion of functional units, cross-linking, and mass transfer of contaminants inside the hydrogel.
[0023] The composite hydrogel material provided by this invention includes a biocolloid capture functional unit; the biocolloid capture functional unit is preferably disposed on the surface of the hydrogel network or extends through the hydrogel network. In this invention, the biocolloid capture functional unit is used to preferentially capture resistant bacteria, extracellular polymers, humic substances, or colloidal particles in water.
[0024] In this invention, the biocolloidal trapping functional unit comprises one or more of the following: cationic groups, zwitterionic groups, polyphenolic adhesive groups, amino groups, guanidinyl groups, quaternary ammonium groups, imidazolium groups, phosphate groups, carboxyl groups, catechol groups, and polysaccharide segments. In this invention, the mass of the biocolloidal trapping functional unit is preferably 1-40% of the dry mass of the hydrogel network, based on 100% of the dry mass. In embodiments of this invention, the mass of the biocolloidal trapping functional unit can be 1%, 2%, 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, or 40% of the dry mass of the hydrogel network. In this invention, the biocolloidal trapping functional unit is preferably immobilized in the hydrogel network by one or more of the following methods: copolymerization, grafting, impregnation adsorption, ionic crosslinking, layer-by-layer assembly, and in-situ polymerization.
[0025] In this invention, when the biocolloidal capture functional unit is amino, the functional component providing the amino group preferably includes one or more of chitosan, carboxymethyl chitosan, amino-modified cellulose, amino-modified alginate, gelatin, polyethyleneimine, polylysine, amino-modified polyvinyl alcohol, amino-modified polyacrylamide, and 3-aminopropyltriethoxysilane modifier.
[0026] In this invention, when the biocolloidal capture functional unit is a quaternary ammonium salt, the functional component providing the quaternary ammonium salt preferably includes one or more of the following: quaternized chitosan, quaternized cellulose, quaternized polyvinyl alcohol, polydimethyldiallyl ammonium chloride, methacryloyloxyethyltrimethylammonium chloride, methacrylamidopropyltrimethylammonium chloride, dimethyldiallyl ammonium chloride, and their polymers, copolymers, and graft modifiers.
[0027] In this invention, when the biocolloidal capture functional unit is a guanidine group, the functional component providing the guanidine group preferably includes one or more of the following: guanidine-modified chitosan, guanidine-modified cellulose, guanidine-modified polyethyleneimine, polyarginine, arginine-grafted polymer, polyhexamethylene guanidine salt, polyhexamethylene biguanide salt, and their modifiers.
[0028] In this invention, when the biocolloidal capture functional unit is a carboxyl group, the functional component providing the carboxyl group preferably includes sodium carboxymethyl cellulose.
[0029] In this invention, when the biocolloidal capture functional unit is a catechol group, the functional component providing the catechol group preferably includes one or more of dopamine, polydopamine, dopamine-grafted chitosan, dopamine-grafted alginate, dopamine-grafted polyvinyl alcohol, catechol-modified cellulose, catechol-modified polyacrylamide, polymerizable monomers containing catechol structures, and their polymers.
[0030] In this invention, when the biocolloidal capture functional unit is a polyphenol adhesive group, the functional component providing the polyphenol adhesive group preferably includes one or more of the following: tannic acid, gallic acid, tea polyphenols, epigallocatechin gallate, lignin polyphenol derivatives, polyphenol-modified chitosan, polyphenol-modified cellulose, and polyphenol-modified alginate.
[0031] In this invention, when the biocolloidal capture functional unit is a zwitterionic group, the functional component providing the zwitterionic group preferably includes one or more of sulfobetaine methacrylate, carboxybetaine methacrylate, 2-methacryloyloxyethyl phosphorylcholine, sulfobetaine acrylamide, carboxybetaine acrylamide, and their polymers, copolymers, and graft modifiers.
[0032] In this invention, when the biocolloidal capture functional unit is a polysaccharide segment, the functional component providing the polysaccharide segment preferably includes one or more of chitosan, carboxymethyl chitosan, sodium alginate, carboxymethyl cellulose, nanocellulose, bacterial cellulose, hyaluronic acid, pectin, carrageenan, xanthan gum, dextran, starch, chitin, and their modifiers.
[0033] The composite hydrogel material provided by this invention includes a contaminant decoupling functional unit; the contaminant decoupling functional unit is preferably disposed after or adjacent to the biocolloid capture functional unit. In this invention, the contaminant decoupling functional unit is used to weaken the electrostatic binding, coordination binding, hydrogen bonding, hydrophobic binding, or biofilm encapsulation between the biocolloid and its carried contaminants, thereby exposing, transferring, or releasing heavy metal ions, organic pollutants, antibiotics, or resistance-related pollutants from the surface of the biocolloid to the fixed region inside the hydrogel.
[0034] In this invention, the associated pollutant decoupling functional unit is a functional group or functional segment fixed on a hydrogel network. The functional group or functional segment preferably includes one or more of the following: carboxyl, phosphate, phosphonic acid, amino, hydroxyl, mercapto, polyphenol, sulfonic acid, methine oxime, iminodiacetic acid, polyphosphate, and hydration regulating groups. In this invention, based on 100% of the dry weight of the hydrogel network, the mass of the associated pollutant decoupling functional unit is preferably 0.5% to 35% of the dry weight of the hydrogel network. In embodiments of this invention, the mass of the associated pollutant decoupling functional unit can be 0.5%, 1%, 2%, 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, or 35% of the dry weight of the hydrogel network. In this invention, the associated pollutant decoupling functional unit is fixed on the hydrogel network, rather than being released into the water in large quantities as a free chelating agent, thus preventing its significant loss during wastewater treatment and ensuring the continuous removal of complex pollutants by the hydrogel material.
[0035] In this invention, the associated pollutant decoupling functional unit is preferably provided by a functional component containing an associated pollutant decoupling functional unit.
[0036] In this invention, when the associated pollutant decoupling functional unit is a carboxyl group, the functional component providing the carboxyl group preferably includes one or more of the following: acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, sodium acrylate, sodium methacrylate, vinyl benzoic acid, polyacrylic acid, polymethacrylic acid, sodium polyacrylate, polyacrylamide-acrylic acid copolymer, carboxymethyl cellulose, carboxymethyl chitosan, sodium alginate, pectin, hyaluronic acid, ethylenediaminetetraacetic acid modified polymer, and diethylenetriaminepentaacetic acid modified polymer.
[0037] In this invention, when the associated pollutant decoupling functional unit is a phosphate group or a phosphonic acid group, the functional component containing the phosphate group or phosphonic acid group preferably includes one or more of the following: vinylphosphonic acid, allylphosphonic acid, phosphate methacrylate, phosphate 2-hydroxyethyl methacrylate, 2-methacryloyloxyethyl phosphorylcholine, phytic acid, sodium phytate, phosphorylated chitosan, phosphorylated cellulose, phosphorylated polyvinyl alcohol, phosphorylated alginate, phosphonic polyacrylic acid, or phosphonic polyethyleneimine.
[0038] In this invention, when the associated pollutant decoupling functional unit is an amino group, the functional component providing the amino group preferably includes one or more of allylamine, ethyleneamine, N-(3-aminopropyl)methacrylamide, dimethylaminoethyl methacrylate, aminoethyl methacrylate, chitosan, carboxymethyl chitosan, gelatin, polyethyleneimine, polyallylamine, polylysine, amino-modified cellulose, amino-modified alginate, amino-modified polyvinyl alcohol, amino-modified polyacrylamide, 3-aminopropyltriethoxysilane modified product, and 3-aminopropyltrimethoxysilane modified product.
[0039] In this invention, when the associated pollutant decoupling functional unit is a hydroxyl group, the functional component providing the hydroxyl group preferably includes one or more of the following: hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, polyvinyl alcohol, cellulose, nanocellulose, bacterial cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methylcellulose, starch, dextran, hyaluronic acid, alginate, and their hydroxyl-modified derivatives.
[0040] In this invention, when the associated pollutant decoupling functional unit is a thiol, the functional component providing the thiol preferably includes one or more of the following: cysteine, N-acetylcysteine, mercaptoacetic acid, mercaptopropionic acid, mercaptoethanol, mercaptoethyl methacrylate, mercaptoethyl acrylate, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, thiolated chitosan, thiolated cellulose, thiolated polyvinyl alcohol, thiolated alginate, and thiolated polyacrylamide.
[0041] In this invention, when the associated pollutant decoupling functional unit is a sulfonic acid group, the functional component providing the sulfonic acid group preferably includes one or more of 2-acrylamide-2-methylpropanesulfonic acid, vinyl sulfonic acid, sodium styrene sulfonate, sodium allyl sulfonate, ethyl methacrylate, ethyl acrylate, sulfonated chitosan, sulfonated cellulose, sulfonated lignin, sulfonated polyvinyl alcohol, sulfonated polystyrene, poly-2-acrylamide-2-methylpropanesulfonic acid, and their salts.
[0042] In this invention, when the associated pollutant decoupling functional unit is a methylamine oxime group, the functional component providing the methylamine oxime group preferably includes one or more of acrylonitrile, methacrylonitrile, acrylonitrile-grafted chitosan, acrylonitrile-grafted cellulose, acrylonitrile-grafted polyvinyl alcohol, polyacrylonitrile, polyacrylonitrile copolymer, methylamine oxime-modified polyacrylonitrile, methylamine oxime-modified chitosan, methylamine oxime-modified cellulose, methylamine oxime-modified polyvinyl alcohol, and methylamine oxime-modified polyacrylamide. In this invention, the nitrile-containing functional component can be converted into a methylamine oxime group under the action of hydroxylamine or hydroxylamine salt.
[0043] In this invention, when the associated pollutant decoupling functional unit is an iminodiacetic acid group, the functional component providing the iminodiacetic acid group preferably includes one or more of the following: iminodiacetic acid, iminodiacetic acid-modified chitosan, iminodiacetic acid-modified cellulose, iminodiacetic acid-modified alginate, iminodiacetic acid-modified polyvinyl alcohol, iminodiacetic acid-modified polyethyleneimine, iminodiacetic acid-modified polyacrylamide, glycidyl methacrylate-iminodiacetic acid graft, chloromethylstyrene-iminodiacetic acid graft, and chelating resin precursor containing an iminodiacetic acid structure.
[0044] In this invention, when the associated pollutant decoupling functional unit is a polyphosphate group, the functional component providing the polyphosphate group preferably includes one or more of sodium tripolyphosphate, sodium hexametaphosphate, sodium polyphosphate, ammonium polyphosphate, polyphosphate, phytic acid, sodium phytate, polyphosphate-modified chitosan, polyphosphate-modified alginate, polyphosphate-modified cellulose, polyphosphate-modified polyvinyl alcohol, and polyphosphate cross-linked polysaccharides.
[0045] The composite hydrogel material provided by this invention includes confined fixation or deactivation functional units; these units are preferably distributed in the inner layer, pore walls, or network cross-linking nodes of the hydrogel network. In this invention, the confined fixation or deactivation functional units are used to fix or deactivate contaminants exposed after decoupling.
[0046] In this invention, the confined fixation or deactivation functional unit comprises a layered composite metal hydroxide. Preferably, the layered composite metal hydroxide is a layered composite bimetallic hydroxide or a layered composite polymetallic hydroxide, wherein at least two metals together constitute the hydroxide layer; the layered composite metal hydroxide preferably comprises at least one divalent metal and one trivalent metal; the divalent metal preferably comprises one or more of Mg, Ca, Zn, Fe, Mn, and Cu; the trivalent metal preferably comprises one or more of Al and Fe; the molar ratio of the divalent metal to the trivalent metal is preferably (2~4):1, more preferably 3:1. In embodiments of the present invention, the layered composite metal hydroxide may include one or more of the following: Mg-Al layered composite bimetallic hydroxide, Zn-Al layered composite bimetallic hydroxide, Ca-Al layered composite bimetallic hydroxide, Mg-Fe layered composite bimetallic hydroxide, Zn-Fe layered composite bimetallic hydroxide, Fe(II)-Fe(III) layered composite bimetallic hydroxide, Mg-Al-Fe layered composite polymetallic hydroxide, and Ca-Al-Fe layered composite polymetallic hydroxide.
[0047] In this invention, the shape of the layered composite metal hydroxide is preferably sheet-like, layered, stacked sheet-like, or assembled in layers; the thickness of the layered composite metal hydroxide is preferably 1~100nm, more preferably 2~50nm, and even more preferably 5~30nm.
[0048] In this invention, with the dry weight of the hydrogel network as 100%, the mass of the confined or deactivated functional units is preferably 2-70% of the dry weight of the hydrogel network. In embodiments of this invention, the mass of the confined or deactivated functional units can be 2%, 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70% of the dry weight of the hydrogel network. In this invention, the confined or deactivated functional units are preferably fixed in the hydrogel network by in-situ deposition, in-situ mineralization, blending crosslinking, surface grafting, pore-confined growth, or ion-induced precipitation.
[0049] In this invention, the water content of the composite hydrogel material is preferably 50-99%; the pore size of the composite hydrogel material is preferably 10 nm-500 μm. In embodiments of this invention, the water content of the composite hydrogel material can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 99%; the pore size of the composite hydrogel material can be 10 nm, 50 nm, 100 nm, 500 nm, 1 μm, 2 μm, 3 μm, 5 μm, 10 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, or 500 μm.
[0050] In this invention, the composite hydrogel material is preferably in the form of blocks, films, spheres, microspheres, granules, fibers, felts, columns, sheets, or fillers. This invention does not impose any particular limitation on the size of the composite hydrogel material; it can be determined based on the technical knowledge of those skilled in the art. In embodiments of this invention, the diameter of the spheres can be 0.5~10 mm; the thickness of the films can be 0.1~10 mm; the thickness of the blocks can be 0.5~30 mm; and the thickness of the felts can be 0.5~30 mm. By controlling the shape of the composite hydrogel material, this invention allows it to fully contact the water to be treated during application.
[0051] A schematic diagram of the composite hydrogel material provided by this invention is shown below. Figure 1 As shown. Figure 1As shown, the composite hydrogel material provided by this invention uses a hydrogel network as its framework. A biocolloidal capture functional unit is used to capture pollutant carriers such as bacteria, resistant bacteria, extracellular polymers, humic substances, and colloidal particles in the water. A concomitant decoupling functional unit is used to weaken the electrostatic, coordination, hydrogen bonding, hydrophobic, and biofilm encapsulation interactions between the pollutant carriers and the heavy metals, metalloids, organic pollutants, or resistance-related pollutants they carry, thereby exposing, transferring, or releasing the concomitant pollutants from the surface of the pollutant carriers. A confinement and inactivation functional unit is used to complex, exchange ions, adsorb, precipitate, mineralize, oxidize, reduce, inhibit, and inactivate the exposed, transferred, or released concomitant pollutants. The biocolloidal capture functional unit, the concomitant decoupling functional unit, and the confinement and inactivation functional unit form a continuous action pathway in the hydrogel material for pollutant carrier capture, concomitant pollutant decoupling, and confinement and inactivation of concomitant pollutants.
[0052] The composite hydrogel material provided by this invention has the following advantages: 1) Composite hydrogel materials can not only treat single free pollutants, but also treat composite pollutants carried by bacteria, resistant bacteria, extracellular polymers, humic substances, and colloidal particles. 2) The composite hydrogel material has a synergistic structure of biocolloid capture functional unit, associated pollutant decoupling functional unit and confined fixation or inactivation functional unit. It can weaken the binding between pollutant carrier and associated pollutant by fixing and decoupling functional unit, so that the associated pollutant is internally confined and fixed or inactivated after exposure. 3) The composite hydrogel material does not require external electric field, low temperature plasma, solar evaporation and condensation or volatile organic compound interception as necessary technical conditions for treating composite pollutants. Instead, the composite pollutants are captured, decoupled and fixed inside the hydrogel material, which requires lower treatment costs. 4) The composite hydrogel material provided by this invention can reduce the risk of co-migration and secondary release of biocolloidal-carried composite pollutants.
[0053] This invention provides a method for preparing the composite hydrogel material described in the above technical solution, comprising the following steps: (1) Mix the hydrophilic polymer material with water to obtain a hydrogel network precursor solution; (2) The hydrogel network precursor solution obtained in step (1), the functional components containing biocolloid capture functional units, the functional components containing associated pollutant decoupling functional units, and the components containing confined fixation or inactivation functional units are mixed to obtain a hydrogel composite system. (3) The hydrogel composite system obtained in step (2) is sequentially molded, crosslinked, washed and activated to obtain a composite hydrogel material.
[0054] This invention mixes hydrophilic polymer materials with water to obtain a hydrogel network precursor solution.
[0055] In this invention, the specific types of hydrophilic polymer materials and water are preferably the same as those described above, and will not be repeated here.
[0056] The present invention does not impose any special limitations on the specific amounts of the hydrophilic polymer material and water, and can ensure that the water content of the composite hydrogel material meets the requirements.
[0057] In this invention, the preferred mixing temperature of the hydrophilic polymer material and water is 20-90°C; the preferred mixing time is 0.5-12 hours; and the mixing of the hydrophilic polymer material and water is preferably carried out under stirring conditions. In embodiments of this invention, the mixing temperature of the hydrophilic polymer material and water can be 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, or 90°C; and the mixing time can be 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, or 12 hours. This invention does not impose a specific limitation on the stirring rate; it is determined based on the technical knowledge of those skilled in the art, as long as a homogeneous and stable solution is formed without splashing. This invention, by controlling the mixing parameters, enables the hydrogel to be homogeneous and stable.
[0058] In this invention, the mass concentration of the hydrophilic polymer material in the hydrogel is preferably 0.5% to 15%. In embodiments of this invention, the mass concentration of the hydrophilic polymer material in the hydrogel can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%. By controlling the concentration of the hydrogel, this invention can control the sparsity of the hydrogel network structure, thereby regulating the mechanical properties and functional release properties of the hydrogel material.
[0059] After obtaining the hydrogel network precursor solution, the present invention mixes the hydrogel network precursor solution, the functional component containing the biocolloid capture functional unit, the functional component containing the associated pollutant decoupling functional unit, and the component containing the confined fixation or inactivation functional unit to obtain a hydrogel composite system.
[0060] In this invention, the functional components containing the biocolloid capture functional unit are preferably the same as those described above, and will not be repeated here.
[0061] In this invention, the functional components containing biocolloidal capture units are immobilized in a hydrogel network through copolymerization, grafting, impregnation adsorption, ionic crosslinking, hydrogen bonding, Schiff base reaction, Michael addition reaction, polyphenol-metal coordination, layer-by-layer assembly, or in-situ polymerization. Preferably, the functional components containing biocolloidal capture units are not released in large quantities into the water to be treated in the form of free small molecules.
[0062] In this invention, the mass of the functional component containing the biocolloid capture functional unit is preferably 1-80% of the dry weight of the hydrogel. In embodiments of this invention, the mass of the functional component containing the biocolloid capture functional unit can be 1%, 2%, 3%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, or 80% of the dry weight of the hydrogel. By controlling the amount of the functional component, this invention can ensure that the dosage of the biocolloid capture functional unit meets the requirements.
[0063] In this invention, the functional components containing the associated pollutant decoupling functional unit are preferably the same as the aforementioned functional components containing the associated pollutant decoupling functional unit, and will not be repeated here.
[0064] In this invention, the functional components containing associated pollutant decoupling functional units are immobilized in a hydrogel network through copolymerization, grafting, amidation, esterification, etherification, Schiff base reaction, Michael addition reaction, silane coupling, ionic crosslinking, hydrogen bonding, metal coordination, layer-by-layer assembly, or in-situ polymerization. In this invention, the associated pollutant decoupling functional units are functional groups or functional segments, and are not released in large quantities into the water body to be treated as free chelating agents.
[0065] In this invention, the mass of the functional component containing the associated pollutant decoupling functional unit is preferably 1-100% of the dry weight of the hydrogel. In embodiments of this invention, the mass of the functional component containing the associated pollutant decoupling functional unit can be 1%, 2%, 3%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, or 100% of the dry weight of the hydrogel. By controlling the amount of the functional component, this invention can ensure that the dosage of the associated pollutant decoupling functional unit meets the requirements.
[0066] In this invention, the component containing the confined fixation or deactivation functional unit is preferably a layered composite metal hydroxide. The specific composition, structure, and size of the layered composite metal hydroxide are preferably the same as described above, and will not be repeated here.
[0067] In this invention, the reaction components preferably include soluble metal salts and structure-directing agents.
[0068] In this invention, the metal ions in the soluble metal salt preferably include Fe. 3+ Fe 2+ Al 3+ Ca 2+ Mg 2+ Mn 2+ Cu 2+ or Zn 2+ One or more of the following; the anion in the soluble metal salt is preferably Cl. - and / or NO3 - .
[0069] In this invention, the structure guiding agent is preferably an alkaline solution, a phosphate solution, a carbonate solution, or a silicate solution.
[0070] In this invention, the alkaline solution is preferably one or more of ammonia water, sodium hydroxide solution, and potassium hydroxide solution; the alkaline solution contains OH... - The concentration is preferably 0.001~5 mol / L, more preferably 0.01~2 mol / L, and even more preferably 0.05~1 mol / L.
[0071] In this invention, the anions in the phosphate solution preferably include H2PO4. - HPO4 2- PO4 3- P2O7 4- and P3O 10 5- One or more of the following; the cations in the phosphate solution preferably include Na. + K + NH4 + Ca 2+ and Mg 2+ The phosphate solution preferably contains one or more of the following: sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, ammonium phosphate, diammonium hydrogen phosphate, sodium pyrophosphate, sodium tripolyphosphate, and sodium hexametaphosphate; the concentration of phosphorus in the phosphate solution is preferably 0.001~2 mol / L, more preferably 0.005~0.5 mol / L, and even more preferably 0.01~0.2 mol / L. In this invention, when the phosphate solution is used to generate hydroxyapatite or calcium phosphate minerals in situ, the molar ratio of Ca to P is preferably 1.0~2.0, more preferably 1.5~1.8.
[0072] In this invention, the anions in the carbonate solution preferably include CO32-. 2- and HCO3 - One or more of the following; the cations in the carbonate solution preferably include Na.+ K + NH4 + Ca 2+ and Mg 2+ One or more of the following: the carbonate solution preferably includes one or more of sodium carbonate solution, sodium bicarbonate solution, potassium carbonate solution, potassium bicarbonate solution, ammonium carbonate solution, ammonium bicarbonate solution, calcium carbonate suspension system, calcium carbonate saturated system, magnesium carbonate suspension system, and magnesium carbonate saturated system; the total concentration of carbonate and bicarbonate in the carbonate solution is preferably 0.001~2 mol / L, more preferably 0.005~0.5 mol / L, and even more preferably 0.01~0.2 mol / L.
[0073] In this invention, the anions in the silicate solution preferably include SiO3. 2- HSiO3 - SiO4 4- and one or more of soluble polysilicates; the cations in the silicate solution preferably include Na. + K + Li + and NH4 + One or more of the following are used: the silicate solution preferably includes one or more of sodium silicate solution, sodium metasilicate solution, potassium silicate solution, lithium silicate solution, ammonium silicate solution, water glass diluent, and silica sol. In this invention, the concentration of the silicate solution, calculated as SiO2, is preferably 0.001~2 mol / L, more preferably 0.005~0.5 mol / L, and even more preferably 0.01~0.2 mol / L.
[0074] In this invention, the amount of soluble metal salt and structure-directing agent added is preferably such that the pH of the reaction system is 8-11 and the mass of the confined or deactivated functional units generated by the reaction is 2-70 wt% of the dry basis mass of the hydrogel. This invention does not have a specific limitation on the order of addition of the soluble metal salt and structure-directing agent; a conventional addition order is acceptable. In embodiments of this invention, the pH value can be 8, 9, 10, or 11. In this invention, the soluble metal salt provides one or more metal ions to enter the hydrogel network, while the added structure-directing agent causes the metal ions to undergo in-situ precipitation, in-situ mineralization, in-situ oxidative hydrolysis, or layered assembly reactions at the hydrogel channels, fiber surfaces, or cross-linking nodes to generate confined or deactivated functional units.
[0075] In this invention, the preferred method for mixing the hydrogel network precursor solution, the functional component containing the biocolloidal capture functional unit, the functional component containing the associated pollutant decoupling functional unit, and the component containing the confined fixation or inactivation functional unit is as follows: first, the hydrogel network precursor solution and the functional component containing the biocolloidal capture functional unit are mixed; then, the functional component containing the associated pollutant decoupling functional unit is added and mixed; followed by the addition of the component containing the confined fixation or inactivation functional unit. Alternatively, the hydrogel network precursor solution and the component containing the confined fixation or inactivation functional unit are mixed first; then, the functional component containing the associated pollutant decoupling functional unit is added and mixed; finally, the component containing the biocolloidal capture functional unit is mixed. By employing different methods for mixing the components, this invention can control the structure of the composite hydrogel material to be a partitioned structure, a gradient structure, or a homogeneous synergistic structure, thereby better treating composite pollutants.
[0076] In this invention, the preferred mixing temperature for the hydrogel network precursor solution and the functional component containing the biocolloid trapping unit is 20-90°C; the preferred mixing time is 0.5-8 hours; and the mixing of the hydrogel network precursor solution and the functional component containing the biocolloid trapping unit is preferably carried out under stirring conditions. In embodiments of this invention, the mixing temperature for the hydrogel network precursor solution and the functional component containing the biocolloid trapping unit can be 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, or 90°C; and the mixing time can be 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, or 8 hours. This invention does not impose a specific limitation on the stirring rate; based on the technical knowledge of those skilled in the art, it is sufficient to form a homogeneous and stable solution without splashing. This invention achieves uniform dispersion by controlling the mixing parameters.
[0077] In this invention, the preferred mixing temperature for adding the functional component containing the associated pollutant decoupling unit is 20-80°C; the preferred mixing time is 0.5-12 hours; and the mixing is preferably carried out under stirring conditions. In embodiments of this invention, the mixing temperature for adding the functional component containing the associated pollutant decoupling unit can be 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, or 80°C; and the mixing time can be 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, or 12 hours. This invention does not impose a specific limitation on the stirring rate; it can be determined based on the technical knowledge of those skilled in the art, as long as it ensures uniform mixing without splashing.
[0078] In this invention, when the component containing the confined or deactivated functional unit is a layered composite metal hydroxide, the mixing time for adding the component containing the confined or deactivated functional unit is preferably 0.5 to 6 hours; the mixing of the component containing the confined or deactivated functional unit is preferably carried out under mechanical stirring or ultrasonic conditions. This invention does not impose special limitations on the mixing temperature or the power of mechanical stirring and ultrasonication; these can be determined based on the technical knowledge of those skilled in the art, as long as uniform dispersion is achieved. In embodiments of this invention, the mixing time for adding the component containing the confined or deactivated functional unit can be 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, or 6 hours. By employing the above methods, this invention enables the confined or deactivated functional unit to be uniformly dispersed in the gel material.
[0079] In this invention, when the component containing the confined or deactivated functional unit contains a soluble metal salt and a structure-directing agent, the preferred method for adding the component containing the confined or deactivated functional unit is to first add the soluble metal salt and mix it evenly, and then add the structure-directing agent for in-situ synthesis. In this invention, the preferred temperature for in-situ synthesis is 20-80°C; the preferred time for in-situ synthesis is 0.5-24 h; and the preferred pH value for in-situ synthesis is 6-11. In embodiments of this invention, the temperature for in-situ synthesis can be 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, or 80°C; and the preferred time for in-situ synthesis can be 0.5 h, 1 h, 2 h, 4 h, 5 h, 6 h, 8 h, 10 h, 12 h, 14 h, 15 h, 16 h, 18 h, 20 h, 22 h, or 24 h. This invention enables metal ions to be synthesized in situ into layered composite metal hydroxides within a hydrogel network under the influence of a structure-directing agent by controlling the parameters of in-situ synthesis.
[0080] After obtaining the hydrogel composite system, the present invention sequentially performs molding, crosslinking, washing and activation on the hydrogel composite system to obtain a composite hydrogel material.
[0081] In this invention, the preferred molding methods are dripping, casting, coating, freeze-thaw, extrusion, die forming, spinning, spray molding, or layer-by-layer assembly. This invention does not impose any specific limitations on the molding operations; hydrogel materials of the desired shape can be obtained using operations well-known to those skilled in the art.
[0082] In this invention, the crosslinking method is preferably ionic crosslinking, chemical crosslinking, physical crosslinking, freeze-thaw crosslinking, photocrosslinking, or composite crosslinking. When a crosslinking agent is required for crosslinking, the crosslinking agent preferably includes one or more of CaCl2, FeCl3, AlCl3, borate, glutaraldehyde, genipin, N,N'-methylenebisacrylamide, persulfate initiation systems, and ultraviolet photoinitiation systems. This invention does not impose a specific limitation on the amount of the crosslinking agent; it can be determined using the technical knowledge of those skilled in the art, as long as it enables crosslinking to be completed. This invention can form a stable hydrogel network through crosslinking.
[0083] In this invention, the crosslinking temperature is preferably 0~80℃; the crosslinking time is preferably 0.1~48h. In embodiments of this invention, the crosslinking temperature can be 0℃, 10℃, 20℃, 30℃, 40℃, 50℃, 60℃, 70℃, or 80℃; the crosslinking time can be 0.1h, 0.5h, 1h, 2h, 3h, 5h, 10h, 12h, 15h, 18h, 21h, 24h, 27h, 30h, 36h, 42h, or 48h. By controlling the crosslinking parameters, this invention can ensure the formation of a stable hydrogel network through crosslinking.
[0084] In this invention, the detergent is preferably deionized water. There is no particular limitation on the amount of detergent used; repeated washing is sufficient as long as the pH of the washing solution reaches 6-8. This invention removes unreacted components and free ions through washing.
[0085] In this invention, the activating agent used for activation is preferably deionized water, a salt solution, or the water to be treated; the cation in the salt solution is preferably Na. + K + Ca 2+ Mg 2+ and NH4 + One or more of the following; the anion in the salt solution is preferably Cl. - SO4 2- NO3 - HCO3 - CO32- H2PO4 - and HPO4 2- One or more of the following: the concentration of the salt solution is preferably 0.001~0.1 mol / L; the water to be treated is the water that needs to be treated in subsequent applications. In embodiments of the present invention, the concentration of the salt solution can be 0.001 mol / L, 0.005 mol / L, 0.01 mol / L, 0.02 mol / L, 0.05 mol / L, 0.08 mol / L, or 0.1 mol / L.
[0086] In this invention, the activation temperature is preferably room temperature; the activation time is preferably 0.5 to 48 hours. In embodiments of this invention, the activation time can be 0.5 hours, 1 hour, 2 hours, 3 hours, 5 hours, 10 hours, 12 hours, 15 hours, 18 hours, 21 hours, 24 hours, 27 hours, 30 hours, 36 hours, 42 hours, or 48 hours. This invention, through activation, can activate functional sites in hydrogel materials.
[0087] A schematic diagram of the preparation process of the composite hydrogel material provided by this invention is shown below. Figure 2 As shown. By Figure 2 As can be seen, the present invention forms a hydrogel network by using hydrophilic polymer materials as the framework of the hydrogel, and then sequentially introduces biocolloid capture functional units, associated pollutant decoupling functional units, and confined fixation or inactivation functional units. Finally, the desired composite hydrogel material is obtained through molding, crosslinking, washing, and activation.
[0088] The present invention also provides the application of the composite hydrogel material described in the above technical solution or the composite hydrogel material prepared by the preparation method described in the above technical solution in water purification.
[0089] In this invention, the water body to be treated for water purification preferably includes one or more of the following: surface water, river and lake water, aquaculture wastewater, sewage treatment plant effluent, pretreated medical wastewater, deeply treated industrial wastewater, decentralized rural sewage, and water bodies containing complex pollutants. In this invention, the complex pollutants in the water body containing complex pollutants preferably include one or more of the following: pollutant carriers, heavy metals or metalloid pollutants, and organic pollutants; the pollutant carriers preferably include one or more of the following: bacteria, resistant bacteria, extracellular polymers, humic substances, and colloidal particles; the heavy metals or metalloid pollutants preferably include one or more of the following: Cr, Cu, Zn, Pb, Cd, U, As, Sb, Hg, and Ni; the organic pollutants include one or more of the following: dyes, phenolic pollutants, nitrogen-containing organic matter, phosphorus-containing organic matter, and resistance-related pollutants. The composite hydrogel material provided by this invention can achieve the capture, decoupling, confined fixation, or inactivation of biocolloidal-carrying complex pollutants in the water body to be treated.
[0090] In this invention, the preferred method of application is to mix the composite hydrogel material with the water to be treated; the mixing time is preferably 0.1~48h; the preferred method of mixing the composite hydrogel material and the water to be treated is direct mixing or mixing the composite hydrogel material with the water after filling it into the device; the device is preferably a fixed bed, filter column, reaction tank, infiltration unit, ecological ditch, artificial wetland packing layer, or circulating water treatment device. In embodiments of this invention, the mixing time can be 0.1h, 0.5h, 1h, 2h, 3h, 5h, 10h, 12h, 15h, 18h, 21h, 24h, 27h, 30h, 36h, 42h, or 48h.
[0091] A schematic diagram illustrating the mechanism of action of the composite hydrogel material provided by this invention in water purification is shown below. Figure 3 As shown. By Figure 3 It can be seen that the composite hydrogel material is based on a three-dimensional network of hydrophilic polymers, constructing biocolloidal capture zones, associated pollutant decoupling zones, and confined fixation zones inside or on the surface of the hydrogel. This allows pollutant carriers such as bacteria, resistant bacteria, extracellular polymers, humic substances, or colloidal particles in the water to be captured first. Subsequently, the binding relationship between the pollutant carriers and heavy metal ions, organic pollutants, or resistance-related pollutants is weakened or destroyed. Finally, the pollutants exposed after decoupling are complexed, adsorbed, exchanged with ions, precipitated, mineralized, reduced, oxidized, inhibited, or inactivated inside the hydrogel, thereby blocking the co-migration and secondary release of biocolloidal-carrying composite pollutants in the water.
[0092] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0093] Example 1 A composite hydrogel material that blocks the co-migration of pollutants carried by biocolloids is composed of: a hydrogel network, a biocolloid capture functional unit, a concomitant pollutant decoupling functional unit, and a confined fixation or inactivation functional unit. The raw material for preparing the hydrogel network is polyvinyl alcohol; the degree of polymerization of the polyvinyl alcohol is 1700~1800, and the degree of alcoholysis is above 98 mol%; the biocolloidal capture functional unit is a quaternary ammonium salt group; the associated pollutant decoupling functional unit is a carboxyl group; the confinement fixation or inactivation functional unit is a Mg-Fe layered composite metal hydroxide (Mg-Fe LDH) nanosheet; the molar ratio of Mg to Fe in the Mg-Fe layered composite bimetallic hydroxide is 3:1; the Mg-Fe layered composite bimetallic hydroxide has a multilayer stacked sheet structure; the thickness of the layered composite metal hydroxide is 5~30 nm; based on the dry basis mass of the hydrogel network as 100%, the mass of the biocolloidal capture functional unit is 20% of the dry basis mass of the hydrogel network, the mass of the associated pollutant decoupling functional unit is 15% of the dry basis mass of the hydrogel network, and the mass of the confinement fixation or inactivation functional unit is 20% of the dry basis mass of the hydrogel network; The preparation method of the composite hydrogel material is as follows: (1) Add 10.0g of polyvinyl alcohol to 107.6g of deionized water and mix for 4h under stirring and 90℃ conditions to obtain a polyvinyl alcohol aqueous solution with a mass concentration of 8.5%, which is used as a precursor liquid for hydrogel network; the degree of polymerization of the polyvinyl alcohol is 1700~1800 and the degree of alcoholysis is 98mol% or more. (2) First, mix the hydrogel network precursor solution obtained in step (1) with 10g of polydimethyl diallyl ammonium chloride aqueous solution, mix for 2h under stirring and 60℃ conditions, then add 1.5g of sodium carboxymethyl cellulose, continue mixing for 3h under stirring and 60℃ conditions, then add 2.0g of Mg-Fe layered composite bimetallic hydroxide, mechanically stir at room temperature for 2h, and ultrasonically disperse for 20min to obtain the hydrogel composite system; the mass concentration of the polydimethyl diallyl ammonium chloride aqueous solution is 20%; (3) The hydrogel composite system obtained in step (2) is molded, then frozen at -20℃ for 12h, then thawed at 25℃ for 4h, and repeated 3 times. After that, it is washed with deionized water until the pH value of the washing solution is 7, and finally activated with deionized water as an activator for 24h to obtain the composite hydrogel material. The pore size of the composite hydrogel material is 10nm~500μm. The composite hydrogel material is a block composite hydrogel material with a thickness of 10mm.
[0094] Application Example 1 The composite hydrogel material provided in Example 1 was mixed with the water to be treated and then treated sequentially for 1 h, 6 h, 12 h, 18 h and 24 h. The water body to be treated is a simulated biocolloid-carrying complex polluted water body, with the following composition: Escherichia coli concentration of 1×10⁻⁶. 7The concentrations were: CFU / mL, humic acid 10 mg / L, Cr(VI) 5 mg / L, tetracycline 1 mg / L, NaCl 10 mmol / L, and pH 7.0. Cr(VI) was prepared from potassium dichromate, tetracycline was used as a co-contaminant, and humic acid was used to simulate natural organic colloidal components.
[0095] Before treatment, the water body to be treated was shaken and equilibrated at 25°C for 12 hours to allow Escherichia coli, humic acid, Cr(VI) and tetracycline to form a biocolloid-carrying complex pollution system. The dry weight ratio of the composite hydrogel material to the volume of the water to be treated is 0.25g:1L, 0.5g:1L, 1g:1L, 2g:1L, 4g:1L and 6g:1L, respectively.
[0096] In Application Example 1, when the treatment time is 24 hours, the purification effect of the composite hydrogel material on the water body to be treated changes with the increase of the composite hydrogel material dosage as follows: Figure 4 As shown. By Figure 4 It can be seen that the treatment effect of the composite hydrogel material increases with the increase of dosage. When the dosage is low, the number of biocolloidal capture functional units, associated pollutant decoupling functional units, and confined fixation or inactivation functional units in the hydrogel material is insufficient, and it cannot fully contact and treat the composite pollutants in the water to be treated. With the increase of dosage, the effective adsorption sites, complexation sites, mineralization sites, and inactivation sites provided by the material increase, the pollutant carrier capture, associated pollutant decoupling, and confined fixation processes are enhanced, and the turbidity, color, COD, heavy metal ion concentration, and bacterial count of the water body all decrease significantly. When the dosage continues to increase to a higher level, the treatment effect gradually tends to plateau because the total amount of pollutants that can be captured and fixed in the water body is limited. Although excessive addition of composite hydrogel material can slightly improve the pollutant removal rate, the unit material utilization efficiency decreases. Therefore, in practical applications, the dosage of composite hydrogel material can be controlled at 0.5~6.0 g / L, preferably 1.0~4.0 g / L, and more preferably 2.0~4.0 g / L, depending on the degree of pollution of the water body to be treated.
[0097] In Application Example 1, when the ratio of the dry weight of the composite hydrogel material to the volume of the water to be treated is 1 g: 1 L, the purification effect of the composite hydrogel material on the water to be treated changes with the increase of treatment time as follows: Figure 5 As shown. By Figure 5It can be seen that after the composite hydrogel material is added to the water to be treated, the state of the water changes from turbid to clear as the treatment time increases. In the initial stage of treatment, the hydrogel material mainly traps biological colloids, bacteria, extracellular polymers, and colloidal particles through surface capture. In the middle stage of treatment, the associated pollutant decoupling functional unit weakens the binding between the pollutant carrier and heavy metal ions or organic pollutants, causing the associated pollutants to be exposed or transferred. In the later stage of treatment, the confinement and fixation or inactivation functional unit adsorbs, complexes, precipitates, mineralizes, redox, inhibits, or inactivates the exposed pollutants, confining the pollutants inside the hydrogel material and reducing their risk of secondary release and co-migration.
[0098] Example 2 A composite hydrogel material for blocking the co-migration of pollutants carried by biocolloids, wherein, based on the dry basis mass of the hydrogel network as 100%, the mass of the biocolloid capturing functional unit is 30% of the dry basis mass of the hydrogel network; the amount of raw materials used in the preparation method is adjusted accordingly, and other conditions are the same as in Example 1.
[0099] Application Example 2 The composite hydrogel material provided in Example 2 was mixed with the water to be treated and then treated for 24 hours. The ratio of the dry weight of the composite hydrogel material to the volume of the water to be treated was 1 g: 1 L. Other conditions were the same as in Application Example 1.
[0100] Example 3 A composite hydrogel material for blocking the co-migration of pollutants carried by biocolloids, wherein, based on the dry basis mass of the hydrogel network as 100%, the mass of the biocolloid capturing functional unit is 40% of the dry basis mass of the hydrogel network; the amount of raw materials used in the preparation method is adjusted accordingly, and other conditions are the same as in Example 1.
[0101] Application Example 3 The composite hydrogel material provided in Example 3 was mixed with the water to be treated and then treated for 24 hours. The ratio of the dry weight of the composite hydrogel material to the volume of the water to be treated was 1 g: 1 L. Other conditions were the same as in Application Example 1.
[0102] Example 4 A composite hydrogel material for blocking the co-migration of pollutants carried by biocolloids, wherein, based on the dry basis mass of the hydrogel network as 100%, the mass of the associated pollutant decoupling functional unit is 25% of the dry basis mass of the hydrogel network; the amount of raw materials used in the preparation method is adjusted accordingly, and other conditions are the same as in Example 1.
[0103] Application Example 4 The composite hydrogel material provided in Example 4 was mixed with the water to be treated and then treated for 24 hours. The ratio of the dry weight of the composite hydrogel material to the volume of the water to be treated was 1 g: 1 L. Other conditions were the same as in Application Example 1.
[0104] Example 5 A composite hydrogel material for blocking the co-migration of pollutants carried by biocolloids, wherein, based on the dry basis mass of the hydrogel network as 100%, the mass of the associated pollutant decoupling functional unit is 35% of the dry basis mass of the hydrogel network; the amount of raw materials used in the preparation method is adjusted accordingly, and other conditions are the same as in Example 1.
[0105] Application Example 5 The composite hydrogel material provided in Example 5 was mixed with the water to be treated and then treated for 24 hours. The ratio of the dry weight of the composite hydrogel material to the volume of the water to be treated was 1 g: 1 L. Other conditions were the same as in Application Example 1.
[0106] Example 6 A composite hydrogel material that blocks the co-migration of pollutants carried by biocolloids, wherein, based on the dry basis mass of the hydrogel network as 100%, the mass of the confined, fixed or inactivated functional units is 50% of the dry basis mass of the hydrogel network; the amount of raw materials used in the preparation method is adjusted accordingly, and other conditions are the same as in Example 1.
[0107] Application Example 6 The composite hydrogel material provided in Example 6 was mixed with the water to be treated and then treated for 24 hours. The ratio of the dry weight of the composite hydrogel material to the volume of the water to be treated was 1 g: 1 L. Other conditions were the same as in Application Example 1.
[0108] Example 7 A composite hydrogel material that blocks the co-migration of pollutants carried by biocolloids, wherein, based on the dry basis mass of the hydrogel network as 100%, the mass of the confined, fixed or inactivated functional units is 70% of the dry basis mass of the hydrogel network; the amount of raw materials used in the preparation method is adjusted accordingly, and other conditions are the same as in Example 1.
[0109] Application Example 7 The composite hydrogel material provided in Example 7 was mixed with the water to be treated and then treated for 24 hours. The ratio of the dry weight of the composite hydrogel material to the volume of the water to be treated was 1 g: 1 L. Other conditions were the same as in Application Example 1.
[0110] Comparative Example 1 A composite hydrogel material omits the biocolloid capture function unit, i.e., it does not add an aqueous solution of polydimethyldiallylammonium chloride; at the same time, the water volume of the system is made up with deionized water, and other conditions are the same as in Example 1.
[0111] Comparative Application Example 1 The composite hydrogel material provided in Comparative Application Example 1 was mixed with the water to be treated and then treated for 24 hours. The ratio of the dry weight of the composite hydrogel material to the volume of the water to be treated was 1 g: 1 L. Other conditions were the same as in Application Example 1.
[0112] Comparative Example 2 A composite hydrogel material omits the associated pollutant decoupling functional unit, i.e., sodium carboxymethyl cellulose is not added, and other conditions are the same as in Example 1.
[0113] Comparative Application Example 2 The composite hydrogel material provided in Comparative Application Example 2 was mixed with the water to be treated and then treated for 24 hours. The ratio of the dry weight of the composite hydrogel material to the volume of the water to be treated was 1 g: 1 L. Other conditions were the same as in Application Example 1.
[0114] Comparative Example 3 A composite hydrogel material, omitting the confinement fixation or deactivation functional unit, i.e., without adding Mg-Fe layered composite bimetallic hydroxide, with other conditions the same as in Example 1.
[0115] Comparative Application Example 3 The composite hydrogel material provided in Comparative Application Example 3 was mixed with the water to be treated and then treated for 24 hours. The ratio of the dry weight of the composite hydrogel material to the volume of the water to be treated was 1 g: 1 L. Other conditions were the same as in Application Example 1.
[0116] When the ratio of the dry weight of the composite hydrogel material to the volume of the water to be treated is 1 g: 1 L and the treatment time is 24 h, the treatment effects of the composite hydrogel materials provided in Application Examples 1-7 and Comparative Application Examples 1-3 are compared as follows: Figure 6 As shown. By Figure 6It can be seen that Application Examples 1 to 7 all exhibited significant reductions in turbidity, COD, heavy metals, and bacterial count, indicating that the composite hydrogel material composed of biocolloidal capture functional units, associated pollutant decoupling functional units, and confined fixation or inactivation functional units can effectively treat biocolloid-carrying composite polluted water bodies. With increasing content of biocolloidal capture functional units, the turbidity removal rate and bacterial count reduction rate significantly improved; with increasing content of associated pollutant decoupling functional units, the COD removal rate and heavy metal removal rate significantly improved; with increasing content of confined fixation or inactivation functional units, the heavy metal removal rate further improved, but when the content was too high, the improvement of some indicators tended to plateau. Compared with the application examples, in Comparative Example 1, omitting the biocolloidal capture functional unit significantly reduced the turbidity removal rate and bacterial count reduction rate; in Comparative Example 2, omitting the associated pollutant decoupling functional unit significantly reduced the COD and heavy metal removal rates; and in Comparative Example 3, omitting the confined fixation or inactivation functional unit significantly reduced the heavy metal removal rate. The above results indicate that the material of the present invention does not rely on a single adsorption process, but rather achieves the blocking of the co-migration process of complex pollutants through a continuous process of pollutant carrier capture, decoupling of associated pollutants, and confined fixation or inactivation of pollutants.
[0117] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A composite hydrogel material that blocks the co-migration of pollutants carried by biocolloids, comprising a hydrogel network, a biocolloid capture functional unit, a concomitant pollutant decoupling functional unit, and a confined fixation or inactivation functional unit; The biocolloid capture functional unit includes one or more of the following: cationic groups, zwitterionic groups, polyphenolic adhesive groups, amino groups, guanidinyl groups, quaternary ammonium groups, imidazolium groups, phosphate groups, carboxyl groups, catechol groups, and polysaccharide segments; The associated pollutant decoupling functional unit is a functional group or functional chain segment fixed on the hydrogel network; The confined fixation or deactivation functional unit includes a layered composite metal hydroxide.
2. The composite hydrogel material according to claim 1, characterized in that, The hydrogel network comprises a hydrophilic polymer material and water.
3. The composite hydrogel material according to claim 1, characterized in that, The biocolloid capture unit is disposed on the surface of the hydrogel network or runs through the hydrogel network.
4. The composite hydrogel material according to claim 1, characterized in that, With the dry weight of the hydrogel network as 100%, the mass of the biocolloid capture functional unit is 1 to 40% of the dry weight of the hydrogel network.
5. The composite hydrogel material according to claim 1, characterized in that, The associated pollutant decoupling functional unit is located after or adjacent to the biocolloid capture functional unit.
6. The composite hydrogel material according to claim 1, characterized in that, With the dry basis mass of the hydrogel network as 100%, the mass of the associated pollutant decoupling functional unit is 0.5~35% of the dry basis mass of the hydrogel network.
7. The composite hydrogel material according to claim 1, characterized in that, The confined fixation or deactivation functional units are distributed in the inner layer, pore walls, or network cross-linking nodes of the hydrogel network.
8. The composite hydrogel material according to claim 1, characterized in that, With the dry basis mass of the hydrogel network being 100%, the mass of the confined, fixed, or deactivated functional unit is 2 to 70% of the dry basis mass of the hydrogel network.
9. A method for preparing the composite hydrogel material according to any one of claims 1 to 8, comprising the following steps: (1) Mix the hydrophilic polymer material with water to obtain a hydrogel network precursor solution; (2) The hydrogel network precursor solution obtained in step (1), the functional components containing biocolloid capture functional units, the functional components containing associated pollutant decoupling functional units, and the components containing confined fixation or inactivation functional units are mixed to obtain a hydrogel composite system. (3) The hydrogel composite system obtained in step (2) is sequentially molded, crosslinked, washed and activated to obtain a composite hydrogel material.
10. The application of the composite hydrogel material according to any one of claims 1 to 8 or the composite hydrogel material prepared by the preparation method according to claim 9 in water purification.